Robust Exponential Synchronization of a Class of Chaotic Systems with Variable Convergence Rates via the Saturation Control. (7th October 2020) - Huang, Meichun; Luo, Runzi; Fu, Jiaojiao; Su, Haipeng
Abstract : This article is concerned with the exponential synchronization of a class of the chaotic systems with external disturbance via the saturation control. Through appropriate coordinate transformation, the exponential synchronization is translated into the asymptotic stability of the error system. By using the Lyapunov stability theory, a novel sufficient condition which possesses the exponential convergence rate λ is presented. The rich choices of the exponential convergence rate λ turn our scheme more general than some existing approaches. Numerical simulations are employed to the Genesio chaotic system and the Coullet chaotic system to illustrate the ability and effectiveness of the presented approach.